KESADARAAN EKOLOGIS DI LINGKUNGAN SEKOLAH DASAR - Wahyuni Purnami; Wigbertus G. Utama; Fransiska J. Madu (PGSD UNIKA SANTU PAULUS RUTENG, 2017)
This study attempts to examine perception, the students’ behavior, and way of managing rubbish at SDK IV, Ruteng Flores NTT. This research is also sought to find out an effective strategy toward internalizing the ecological awareness to the primary students. The research product is the strategy of managing rubbish at the school environment, which is also recommended to other institutions. The data were obtained through questionnaire, interview, observation, and treatment as well as document review. The data were descriptively analyzed through data reduction, data display, and conclusion drawing. The research revealed that the school employed a self- management of rubbish involving the students, the teachers, and the staffs. The students’ perception increased from 60.27% to 83 %. The findings indicated that the internalization treatment improve the students’ perception and ecological awareness toward rubbish management at the school.